Efficient Protosilylation of Unsaturated Compounds with Silylboronates over a Heterogeneous Cu3N Nanocube Catalyst - Xu, Hang; Yamaguchi, Sho; Mitsudome, Takato; Mizugaki, Tomoo (Synlett, 2023)
Copper-catalyzed protosilylation of unsaturated compounds with silylboronates has attracted attention for the production of organosilanes; however, the use of organic ligands or bases is unavoidable. Herein, we report a heterogeneous catalytic system for the protosilylation of unsaturated compounds with silylboronates under mild and additive-free conditions over copper nitride nanocubes (Cu3N NCs). This method can be applied to various substrates (e.g., alkynes, alkenes, or imines) to afford the corresponding organosilicon compounds. The Cu3N NC catalyst can be easily recovered and reused several times. Thus, the active and reusable Cu3N NC catalyst offers a green and sustainable method for efficient organosilane production.
Keywords: protosilylation; alkenes; alkynes; silanes; copper catalysis; heterogeneous catalysis; copper nitride